2016
DOI: 10.2337/db15-1633
|View full text |Cite
|
Sign up to set email alerts
|

A Reevaluation of the Role of the Unfolded Protein Response in Islet Dysfunction: Maladaptation or a Failure to Adapt?

Abstract: Endoplasmic reticulum (ER) stress caused by perturbations in ER homeostasis activates an adaptive response termed the unfolded protein response (UPR) whose function is to resolve ER stress. If unsuccessful, the UPR initiates a proapoptotic program to eliminate the malfunctioning cells from the organism. It is the activation of this proapoptotic UPR in pancreatic β-cells that has been implicated in the onset of type 2 diabetes and thus, in this context, is considered a maladaptive response. However, there is gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 86 publications
(120 reference statements)
5
46
0
1
Order By: Relevance
“…This was consistent with our finding of reduced ER stress capacity in prediabetic rats (Fig. 2) (Bellmann et al 1997, Herbert & Laybutt 2016. Downregulation of Plin2 is associated with decreased ER stress and prevention of β-cell apoptosis (Chen et al 2017), and it was increased in 60-day BBdp rats.…”
Section: Journal Of Endocrinologysupporting
confidence: 91%
See 1 more Smart Citation
“…This was consistent with our finding of reduced ER stress capacity in prediabetic rats (Fig. 2) (Bellmann et al 1997, Herbert & Laybutt 2016. Downregulation of Plin2 is associated with decreased ER stress and prevention of β-cell apoptosis (Chen et al 2017), and it was increased in 60-day BBdp rats.…”
Section: Journal Of Endocrinologysupporting
confidence: 91%
“…High insulin production in response to fluctuating glucose makes pancreatic islets particularly susceptible to ER stress due to protein misfolding. Unresolved or sustained ER stress can invoke programmed cell death (Pirot et al 2007, Pino et al 2009, Brozzi & Eizirik 2016, Herbert & Laybutt 2016, Szabat et al 2016. Increased ER stress response-related genes in neonatal pancreas were associated with a corresponding increase in proapoptotic genes but decreased levels of caspase-1 and cleaved caspase-3 compared with control animals.…”
Section: Journal Of Endocrinologymentioning
confidence: 99%
“…The fine-tuning of this adaptive response is vital for the preservation of the β-cell differentiated phenotype. Indeed, our and others recent evidence indicated that the failure of adaptive UPR is associated with the progression to diabetes and altered β-cell differentiation (Herbert & Laybutt 2016) (see 'The loss of β-cell differentiation in diabetes: causes and mechanisms' section).…”
Section: Figurementioning
confidence: 94%
“…This led to the hypothesis that β-cell dysfunction in T2D may result from a failure of the UPR to adequately adapt rather than from a maladaptive UPR (Herbert & Laybutt 2016). By comparing timedependent gene expression changes in islets of diabetesprone (db/db mice on C57BL/KsJ genetic background) and diabetes-resistant (ob/ob mice on C57BL/6J genetic background) mouse models of obesity, we observed in ob/ob mice a progressive upregulation of adaptive UPR genes, including Hspa5, Fkbp11 and Dnajc3, in parallel with the maintenance of increased spliced/total Xbp1 (Xbp1s/t) mRNA ratio.…”
Section: Journal Of Endocrinologymentioning
confidence: 99%
“…Despite the strong association between ER stress and diabetes, the mechanism by which PERK regulates diabetes-related genes and the role of ER stress in the development of the disease are still largely unknown. Nevertheless, the failure of the UPR to restore homeostasis can become harmful to pancreatic β cells by eventually initiating apoptosis, thereby reducing insulin secretion, and contributing to T2D pathogenesis 22 .…”
Section: Introductionmentioning
confidence: 99%